Growth and characterization of nanocrystalline PbS:Li thin films. (October 2016) - Portillo, M. Chávez; Mathew, X.; Juárez Santiesteban, H.; Pacio Castillo, M.; Portillo Moreno, O.
Abstract: The structural, electrical and opto-electronic properties of PbS thin films doped with Li + ion were investigated. The crystallite size showed a strong dependence on Li doping, the crystal size changed from 36 nm to 12 nm due to Li incorporation in PbS. Optical band gap showed a shift in the range ∼1.5–2.3 eV with Li incorporation. Urbach tailing in the band gap was observed and the Urbach energy has a dependence on the amount of incorporated Li. SEM images showed a notable change in grain size with Li doping, however the morphology changes from large grains to agglomerations of smaller grains when doped with Li. The electric conductivity of the films showed a dependence on Li doping, reached a maximum value and later decreased for higher Li containing films. The doped samples showed better photosensitivity. Highlights: PbS and PbS:Li thin films were obtained by Chemical bath method. PbS nanocrystals of diameter of 36–12 nm were grown due to Li incorporation in PbS. Optical band gap of nanocrystals films varied from 1.5 to 2.3 eV. The PbS: Li doped demonstrated superior photosensivity.